MONITORING OF WATER RESOURCES AND CREATION OF CARDS ON THE BASIS OF GEOGRAPHICAL INFORMATION SYSTEMS AND TECHNOLOGIES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In this article, Geographic Information Systems (GAT) monitoring of the status of the Ep octi cuvlapi is carried out in accordance with its functions and at the level of production. accountability and investigation are outlined.